IMPLEMENTASI PENDIDIKAN KARAKTER MELALUI PEMBELAJARAN PPKn SEBAGAI UPAYA PENCEGAHAN DAMPAK SOSIAL JUDI ONLINE PADA SISWA SMA NEGERI 9 MERANGIN - Dara Viona Utania; Budi Juliardi; Indra Rahmat (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2026)
The increasing practice of online gambling among adolescents has led to various social effects, such as decreased academic motivation, discipline, responsibility, and the quality of student interactions. The purpose of this study is to describe the implementation of character education through the study of Pancasila and Civic Education (PPKn) as an effort to prevent the social impact of online gambling for students of SMA Negeri 9 Merangin, as well as to identify factors that support and prevent its implementation. The research uses a qualitative approach with a descriptive approach. Data was obtained through observations, interviews, and documentation of PPKn teachers, Guidance and Counseling teachers, homeroom teachers, Religious Education teachers, and students. Data analysis is carried out using the Miles and Huberman model which includes data reduction, data presentation, and conclusions to be drawn. The results of the study show that the implementation of character education is carried out by integrating character values with PPKn learning, teacher examples, habituation of positive behavior, religious activities, student coaching, and providing education about the risks of online gambling. The implementation contributes to increasing students' awareness of the negative impact of online gambling from academic, social, economic, and psychological aspects. Supporting factors include teacher loyalty, collaboration between school residents, coaching activities, and religious education, while inhibiting factors include suboptimal parental supervision, the influence of the social environment, uncontrolled use of gadgets, low student awareness, and limited school supervision outside the learning environment. This study emphasizes that the implementation of character education through PPKn learning plays an important role in preventing the impact of online gambling on society and requires synergy between schools, families, and the community so that student character development takes place optimally.